2020
DOI: 10.1161/hypertensionaha.120.15346
|View full text |Cite
|
Sign up to set email alerts
|

C-allele of rs4769613 Near FLT1 Represents a High-Confidence Placental Risk Factor for Preeclampsia

Abstract: The variant rs4769613 T/C within the enhancer element near FLT1 , an acknowledged gene in preeclampsia, was previously identified as a risk factor for preeclampsia in the genome-wide association study (GWAS) targeting placental genotypes. We aimed to test the robustness of this association in 2 Estonian cohorts. Both placental sample sets HAPPY PREGNANCY (Development of novel non-invasive biomarkers for fertility and healthy pregnancy; preeclampsia, n=44 versus nonpreeclampsia, n=1724) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Indeed, the precise combination of transcriptional regulators that bind at the regulatory elements of the FLT1 locus are not well understood. However, a few studies have highlighted the importance of FLT1 cis -regulatory elements and suggested that disruptions in these non-coding regulators affect gene expression of FLT1 and its isoforms and can ultimately lead to disease (26,28,37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the precise combination of transcriptional regulators that bind at the regulatory elements of the FLT1 locus are not well understood. However, a few studies have highlighted the importance of FLT1 cis -regulatory elements and suggested that disruptions in these non-coding regulators affect gene expression of FLT1 and its isoforms and can ultimately lead to disease (26,28,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the FLT1 genes leads to vascular abnormalities and cardiovascular phenotypes in fish, mice and humans (23)(24)(25). Despite extensive study of FLT1 function, its regulatory network of enhancers has not been completely defined (26)(27)(28). How perturbations of these elements may alter the transcriptional regulation of FLT1 has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The subgroup of ‘REPROMETA proven fathers’ (n=311) was recruited in 2006-2011 at the Women’s Clinic at Tartu University Hospital during the REPROMETA study (PI: M. Laan), originally designed to collect mother-father-placenta trios at delivery to investigate genetics of pregnancy complications ( 43, 44 ). In this study, the REPROMETA fathers represented reference men with proven fertility.…”
Section: Methodsmentioning
confidence: 99%
“…The reference sample of Estonian men (n=1,134) comprised healthy young men (n=499) and subjects with proven fatherhood (n=635) ( Table 1, Table S1). The cohort of 'Estonian young men' (n=499) was to collect mother-father-placenta trios at delivery to investigate genetics of pregnancy complications (43,44). In this study, the REPROMETA fathers represented reference men with proven fertility.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation